Co-developing climate-responsive propositions for aquatic food systems in the Bengal Delta to influence transformative policies and investments - Hossain, Peerzadi; Barman, Benoy; Nahiduzzaman, Md (WorldFish, 2024)
As the world’s largest delta, the Bengal Delta is a key source of aquatic foods for about 170 million people living in Bangladesh. However, aquatic food systems in the delta are highly vulnerable to climate change because of the region’s geographical and environmental setting, which is largely affected by sea-level rise and interannual climate variabilities. As such, climatic shocks and stresses, together with poor infrastructural, socioeconomic and ecological factors in the coastal belt of the country, diminish the ability of small-scale aquatic food producers to tackle climate risks. To help develop inclusive climate-responsive aquatic food systems in the region, we initiated policy dialogues with sectoral experts and stakeholders and reviewed a range of documents, starting from current national fisheries policies, strategies and plans, through ongoing research and development (R&D) programs, to global policy recommendations. In doing so, we used a qualitative method to assess reviewed documents before the policy dialogues and then to evaluate the dialogues themselves afterward. The results combine local-level insights from the dialogues, national-level learnings from the R&D programs and a global call to action that has gained momentum for aquatic food systems. We co-developed five key climate-responsive policy propositions to influence ongoing revision of the Bangladesh government’s national fisheries policy from 1998. These propositions hold significant potential to help develop sustainable and resilient aquatic food systems, influence the investment framework and, thus, strengthen the growing worldwide footprint of the Bengal Delta’s blue economy.